Prevention of musculoskeletal disorders within management systems: A scoping review of practices, approaches, and techniques. (November 2015) - Yazdani, Amin; Neumann, W. Patrick; Imbeau, Daniel; Bigelow, Philip; Pagell, Mark; Wells, Richard
Abstract: The purpose of this study was to identify and summarize the current research evidence on approaches to preventing musculoskeletal disorders (MSD) within Occupational Health and Safety Management Systems (OHSMS). Databases in business, engineering, and health and safety were searched and 718 potentially relevant publications were identified and examined for their relevance. Twenty-one papers met the selection criteria and were subjected to thematic analysis. There was very little literature describing the integration of MSD risk assessment and prevention into management systems. This lack of information may isolate MSD prevention, leading to difficulties in preventing these disorders at an organizational level. The findings of this review argue for further research to integrate MSD prevention into management systems and to evaluate the effectiveness of the approach. Highlights: There was little information on the integration of MSD prevention into management systems in the peer-reviewed literature. Incorporating MSD prevention into organizational level approaches could improve production in addition to preserving workers' health in workplaces. MSD hazard assessment and risk prevention are partially outside of the main management processes. Bringing ergonomics as a means of preventing MSD into organizations' management systems appears to be highly desirable.